2022
DOI: 10.3389/fimmu.2021.795232
|View full text |Cite
|
Sign up to set email alerts
|

Applications and Immunological Effects of Quantum Dots on Respiratory System

Abstract: Quantum dots (QDs), are one kind of nanoscale semiconductor crystals with specific electronic and optical properties, offering near-infrared mission and chemically active surfaces. Increasing interest for QDs exists in developing theranostics platforms for bioapplications such as imaging, drug delivery and therapy. Here we summarized QDs’ biomedical applications, toxicity, and immunological effects on the respiratory system. Bioapplications of QDs in lung include biomedical imaging, drug delivery, bio-sensing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…miR-185 and miR-34b are potential targets for lung cancer treatment. Furthermore, QDs conjugated with Camellia sinensis leaf extract were shown to inhibit the lung tumor cell cycle and decrease cancer cell viability [ 51 ]. In another study, the treatment of uncapped CdTe nanoparticles (520Q and 580Q) induced oxidative stress in lung tumors and human bronchial epithelial cells.…”
Section: Commonly Used Nanoparticles In Cancer Diagnosismentioning
confidence: 99%
“…miR-185 and miR-34b are potential targets for lung cancer treatment. Furthermore, QDs conjugated with Camellia sinensis leaf extract were shown to inhibit the lung tumor cell cycle and decrease cancer cell viability [ 51 ]. In another study, the treatment of uncapped CdTe nanoparticles (520Q and 580Q) induced oxidative stress in lung tumors and human bronchial epithelial cells.…”
Section: Commonly Used Nanoparticles In Cancer Diagnosismentioning
confidence: 99%
“…Furthermore, surface modification can modify the hydrophobicity, charge, biocompatibility, and other properties of QDs, which may ultimately impact their distribution and targeting in biological systems. [44] Since its first discovery in 1983, with the continuous development of QD preparation technology, the types of QDs have gradually expanded to carbon QDs, [45] graphene QDs, [46] and polymer QDs, [47] showing potential applications in biomedical research. QDs possess some obvious advantages over organic fluorescent dyes, like quantum effects, excitation spectrum width, emission spectrum narrowness, high molar extinction coefficient, strong anti-light bleaching properties, difficult chemical degradation, long fluorescence lifetime, and emission color changes with particle size.…”
Section: Quantum Dot Labelsmentioning
confidence: 99%
“…The quantum confinement effect is stronger in smaller crystals, resulting in a shorter fluorescence emission wavelength and a higher fluorescence quantum yield. Furthermore, surface modification can modify the hydrophobicity, charge, biocompatibility, and other properties of QDs, which may ultimately impact their distribution and targeting in biological systems [44] …”
Section: Quantum Dot Labelsmentioning
confidence: 99%
“…12 There are a lot of studies that have confirmed the uptake of QDs and demonstrated their translocation in various organisms. 7,11,13,14 While aquatic organisms are often used in studies assessing toxicological and ecotoxicological risk due to the sensitivity of their physiological processes (especially photosynthesis) to pollutants and the simplicity of cultivation, there are few works 11,15,16 related to the study of the internalization and toxicity of metal-based QDs to algae, which become one of the first targets of QDs in the aquatic environment. Algae are capable of accumulating various contaminants, including heavy metals, and often serve as model organisms for more complex plants in studies to assess the toxic effects of substances on ecosystems and global environmental processes.…”
Section: Introductionmentioning
confidence: 99%